Fulfillment Matter of Education Rights of Children in Conflict With the Criminal Law - Nurhamdah Nurhamdah; Emilia Mustary; Fikri Fikri; Subhan Saleh; Nabilahumaida Nabilahumaida (Jurnal Ilmiah Al-Syir'ah, 2022)
This study aims to determine the forms of the fulfillment of education rights for children in conflict with the criminal law in Indonesia through the "Independent School" program and the factors hindering its practice. It was field research in the form of a case study with data collection techniques: observation and interviews. The research findings reveal that the fulfillment of the right to education for children conflicts with the criminal law (ABH) already carried out but not optimally as regulated in Permen PPPA No. 15 of 2010. This can be seen from the efforts of the staff at LPKA to open non-formal classes even though they do not have adequate classrooms and facilities and the unavailability of professional teaching staff. The inhibiting factor is the absence of human resources in the form of professional teaching staff and limited facilities and infrastructure. As a result, the implementation of education did not work well because the teaching staff did not have an official educational background, and teaching activities were only performed as additional duties as staff at LPKA. The study results show that the LPKA staff's role is vast in providing education to ABH regularly to fulfill education rights. The implications are expected to become input for the LPKA Class II Maros policy to provide management and learning techniques to staff and input for the central government to recruit teaching staff and social workers as well as the provision of facilities and infrastructure.